Insight into the mechanical integrity of few-layers graphene upon lithiation/delithiation via in situ monitoring of stress development. (July 2015) - Sonia, Farjana J.; Ananthoju, Balakrishna; Jangid, Manoj K.; Kali, Ravi; Aslam, M.; Mukhopadhyay, Amartya
Abstract: By monitoring the stress developments in situ during lithiation/delithiation of few layers graphene films, we report here for the first time an interesting observation of stress release/reversal just within the potential ranges corresponding to the co-existences of pristine graphene, dilute stage I and stage IV Li-graphite intercalation compounds (Li-GICs). This, along with supporting observations related to the presence of cracks in the graphene films upon electrochemical cycling and enhanced I D / I G ratio in Raman spectra recorded upon cycling primarily within the potential regimes corresponding to the stress release/reversal, indicate possible occurrences of mechanical/structural degradation mainly during the initial stages of lithiation and later stages of delithiation. This observation is being supported by a geometric model which estimates the strains induced in the individual graphene layers at the interfaces between the different Li-GICs at the various stages of lithiation; and as a function of distance from the current collector. On a slightly different note, the experimentally recorded magnitude of net lithiation induced reversible in-plane stress development was ∼11 GPa. This is in fair agreement with that expected based on the theoretical dilation of ∼1% along the graphene layers upon lithiation as per the classical Li-intercalation mechanism (i.e., up to formation of LiC6 ).